Caesalpinia sappan L. ethyl acetate extract regulated angiogenesis in atherosclerosis by modulating the miR-126/VEGF signalling pathway - Yue He; Chao Huang; Jingjing Chen; Weizeng Shen (Heliyon)
Aims of the study: To investigate the regulatory mechanism of Caesalpinia sappan L. ethyl acetate extract (CSEAE) on angiogenesis in atherosclerosis (AS) based on the miR-126/VEGF signalling pathway. Materials and methods: Our study first screened for differentially expressed microRNAs (miRNAs) associated with AS using the Gene Expression Omnibus (GEO) public database at the National Center for Biotechnology Information (NCBI) and R language software. Subsequently, our study verified the target-regulatory relationship between miR-126 and vascular endothelial growth factor (VEGF) in human umbilical vein endothelial cells (HUVECs) by using the “TargetScan” website and dual-luciferase reporter assay. In cellular experiments, Our study used cell proliferation assays and flow cytometry to assess the effects of CSEAE-Mediated serum on the proliferation and apoptosis of HUVECs. In animal experiments, our study used HE staining, Oil Red O staining and immunohistochemistry (IHC) staining to detect plaque area/lumen area (%), lipid area/plaque area (%) and microvessel density (MVD) in mouse aortas. In addition, our study performed RT‒PCR, ELISA and Western blot assays in ex vivo and in vivo experiments. Results: A total of 39 differentially expressed miRNAs of AS were identified, among which the miR-126 expression level was significantly downregulated. Dual luciferase reporter gene assay results showed that miR-126 and VEGF have a targeting relationship, and the miR-126 mimic could inhibit the luciferase activity of the wild-type VEGF reporter gene vector (p value < 0.01). In cellular experiments, cell proliferation assays and flow cytometry results showed that CSEAE-Mediated serum significantly increased the proliferative activity after 24–72 h of treatment (p-value <0.01) and decreased the apoptotic level of HUVECs (p value < 0.01), and RT‒PCR results showed that CSEAE-Mediated serum significantly upregulated the expression of miR-126 (p value < 0.01) and downregulated the expression of VEGF mRNA in HUVECs (p value < 0.01). In vivo experiments, HE staining and IHC staining showed that CSEAE significantly reduced the MVD in the aorta and plaques of mice (p value < 0.01) and significantly reduced the aortic plaque area/lumen area (%) (p value < 0.01). Moreover, RT‒PCR assay and Western blot analysis results showed that CSEAE significantly upregulated the expression of miR-126 (p value < 0.01), downregulated the expression of VEGF mRNA (p value < 0.01), and decreased the protein expression levels of VEGF (p value < 0.01), phosphatidyl-inositol-3-kinase (PI3K) (p value < 0.01), and Ser/Thr-protein kinase (AKT1) (p value < 0.01) in mouse aortas, while ELISA showed that CSEAE significantly reduced the serum levels of vascular endothelial growth factor receptor (VEGFR2) (p value < 0.01) and hypoxia-inducible factor-1 (HIF-1) (p value < 0.01) in mice. Conclusion: This study emphasises CSEAE as a natural medicinal extract for the treatment of AS that can improve the migratory viability and reduce the apoptosis of HUVECs to maintain the health of the arterial endothelial microenvironment, while CSEAE also inhibits angiogenesis and delays plaque formation in ApoE−/− mice, suggesting that the therapeutic effect of CSEAE for AS may be related to its inhibition of neovascularisation and that its molecular mechanism may be related to the miR-126/VEGF signalling pathway.